Prophylactic Ureteral Catheter Placement Appears to Reduce Intraoperative Ureteric Injury During Resection of Primary Retroperitoneal Liposarcoma - Xiaobing Chen MD; Jun Chen MD; Ferdinando Carlo Maria Cananzi MD; Wenjie Li MD; Vittorio Quagliuolo MD; Chenghua Luo MD, PhD; Yinmo Yang MD, PhD (Technology in Cancer Research & Treatment, 2022)
Background: Prophylactic ureteral catheters placement (PUCP) was advocated as an effective strategy for decreasing ureteral morbidities in colorectal surgeries. However, whether it should be routinely used prior to primary retroperitoneal liposarcoma (PRLS) surgeries remains unknown. Methods: It was a retrospective study, conducted at a tertiary sarcoma center. Medical records of patients with PRLS undergoing surgeries from January 2015 through December 2018 were reviewed. Primary endpoint was the rate of ureteral morbidities during and after retroperitoneal liposarcoma resection procedures. Univariate and multivariate analyses determined risk factors associated with ureteral injury (UI) in patients undergoing surgeries. Results: A total of 55 patients of PRLS were included. Fourteen (25.5%) patients underwent PUCP, with 1 UI (7.1%) identified. In 41 patients with no PUCP, 15 (36.6%) exhibited UIs during and post surgeries. There were significant improvements of UIs in group PUCP, compared with patients without PUCP ( P  < .05). Resection surgeries combined with colectomy and tumor-ureter relationship were 2 risk factors significantly associated to UIs ( P  < .01). Conclusions: PUCP might be an effective way of preventing UIs in patients with PRLS. It could be suggested especially in patients with ureter encased by tumor or anticipated colectomy during the surgical process.